Pelatihan Peran Inovasi, E-Commerce, Ekosistem Mendorong Inovasi Produk Unggulan Desa - Lesi Hertati; Asmawati Asmawati; Lili Syahfitri; Rum Hendarmin (STAI Auliaurrasyidin Tembilahan, 2022)
This community service aims to train the UMKM of Musi Banyuasin village for product creativity from a village to produce superior products of the highest quality and can be marketed through a more modern way, namely e.commerce. The method applied is lectures and direct practice, the benefits of E-commerce are quite helpful, namely online shopping, humans no longer have to go to shopping centers. The output of this service activity adds to the knowledge and expertise of Village MSMEs in selling village handicrafts. Visiting e-commerce sites, and shopping for all completed transactions and goods until your doorsteps. The various conveniences of E-Commerce, being able to start an e-commerce business is a promising business so you don't need to hesitate to try it. The Village Innovation Program (PID) increases rural productivity by relying on local economic development and entrepreneurship, both in the realm of community business development, as well as businesses initiated by the Village through Village-Owned Enterprises and Joint Village-Owned Enterprises, as well as Village Leading Products (Prudes ) and Superior Products for Rural Areas (Prukades) to drive and develop the Village economy. Improving the quality of human resources (This link between rural productivity and the quality of human resources is expected to occur in the short term as well as significant impacts in the long term through investment in basic education and health.